Financial accounting as a second language - Weiner, David P. (Hoboken, NJ : John Wiley & Sons, 2009)
This book introduces the language of accounting, explains the core concepts of accounting, and teaches how to apply these core concepts to solve accounting problems. Developed by David Weiner through his forty year teaching career, this text is filled with study skills, techniques, and strategies used help students learn the core concepts of accounting and get the grades they deserve.
Includes index, glossary and appendices.
Keywords: Accounting; Accounting -- Study and teaching; Accounting -- Handbooks, manuals, etc